2012
DOI: 10.1128/aac.06307-11
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Human Immunodeficiency Virus Type 1 Activity of Novel 6-Substituted 1-Benzyl-3-(3,5-Dimethylbenzyl)Uracil Derivatives

Abstract: ABSTRACTNonnucleoside reverse transcriptase (RT) inhibitors (NNRTIs) are important components of current combination therapies for human immunodeficiency virus type 1 (HIV-1) infection. In screening of chemical libraries, we found 6-azido-1-benzyl-3-(3,5-dimethylbenzyl)uracil (AzBBU) and 6-amino-1-benzyl-3-(3,5-dimethylbenzyl)uracil (AmBBU) to be highly active and selective inhibitors of HIV-1 replicationin vitro. To determine the resistance profiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…Indeed, drugs that target the RNA polymerases of HIV and other eukaryotic viruses select for escape mutations that increase viral replication rates [57], [58]. Growing arboviruses only in an arthropod cell line, rather than switching between their arthropod and vertebrate hosts, selects for substitutions that increase the production of the reverse transcriptase needed for genome replication [59].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, drugs that target the RNA polymerases of HIV and other eukaryotic viruses select for escape mutations that increase viral replication rates [57], [58]. Growing arboviruses only in an arthropod cell line, rather than switching between their arthropod and vertebrate hosts, selects for substitutions that increase the production of the reverse transcriptase needed for genome replication [59].…”
Section: Discussionmentioning
confidence: 99%
“…The MKC-442 (emivirine) has HEPT origins ( Figure 3 ), even if it was very promising, it was abandoned after phase III of clinical trials [ 10 , 14 , 15 , 28 ].…”
Section: Smiles Of Anti-hiv Pyrimidinesmentioning
confidence: 99%
“…The INI inhibitor: raltegravir (RAL, MK-0518) [ 12 , 13 , 14 , 15 , 17 , 18 , 19 , 24 ] (see Figure 1 ) [ 9 , 10 , 11 , 12 , 13 , 14 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 We also continued the search for an anti-HIV-1 agent using the structure-activity relationships of the 1,3-disubstituted and 1,3,6-trisubstituted uracils. [11][12][13][14][15][16] We have demonstrated that the 3,5-dimethylbenzyl group at the N 3 -position and the amino group at the C6-position of the uracil skeleton play an important role in enhancing the anti-HIV-1 activity. Notably, substitution at the 1-position (with a benzyl or 4-picolyl group) of 6-amino-3-(3,5-dimethylbenzyl)uracil to obtain 1a-b (Table 1) yielded satisfactory anti-HIV-1 activity, with EC 50 values of 0.07 AE 0.01 mM and 0.03 AE 0.03 mM, respectively.…”
Section: Introductionmentioning
confidence: 99%